'IT'S NOT OVER 'TIL IT'S OVER…' CREATIVE THERAPY AND PARTNERSHIP WORKING AT WILLOWBROOK HOSPICE. Issue Volume 4: Issue (2014)Supplement 1 (1st March 2014) - Scriven, Lucy; Gallagher, Lisa
Abstract : Background & Aims: This creative therapy project raises awareness for the 2013 National Dying Matters Campaign. It's an experimental collaboration between hospice patient and artist Julie Williams, local artist Chantelle Townley, Advance Care Planning Facilitator, Lisa Gallagher and Holistic Therapist Lucy Scriven. Funding was kindly provided by St Helens Council. The artwork collage, entitled 'It's Not Over 'Til It's Over…' depicts the richness of Julie's life using beautiful photographs, steeped in memories and personal story telling. Safety measures over the five outpatient sessions included: on-going discussion and emotional support, regular 'time outs' to reduce impact on lethargy, and positive reflection. The artwork was officially unveiled at a celebration, in essence a living wake, hosted at Willowbrook, attended by family, friends and the local press. Results: Strengthened interdepartmental working within Willowbrook. Stronger links for partnership working in the local community. Promotion of the value of creative therapies for patients and families. Promotion of the Dying Matters Campaign, and advance care planning within the hospice, locally and nationally. Conclusion: This project has helped to raise awareness for the Dying Matters Campaign; it's also strengthened partnership working within the hospice and with the local community. Through artistic expression Julie was helped to share with the world everything she held dear and has been of great value in connecting positively with meaning in her life. Julie experienced the opportunity to develop her undiscovered artistic potential, and explore new coping strategies by moving away from denial into a place of acceptance. Importantly, through participation with the project, Julie actively engaged in her end of life care planning and inspired others to also engage. She also created a celebratory legacy that will now support her loved ones in their sadness and grief.